Indexing Social Security: An Analysis of the Issues - Kaplan, Robert S. (Washington : American Enterprise Institute for Public Policy Research, 1977)
The financial difficulties facing the social security system have received extensive publicity in recent years. It is the purpose of this study to identify the options available for remedying the indexing error and examine the consequences of the various reform proposals now under consideration in terms of future costs, future benefits, and implementation problems.
Includes bibliographical references.
ne 11/05/2018
Loan
Keywords: Social Security